Expatriate leaders of international development projects : creating success in an unforgiving environment - McLaughlin, Patricia J. (Emerald Publishing Limited, 2021)
Drawing on the experiences of six expatriate leaders who, collectively, had more than 78 years of experience managing United States Agency for International Development (USAID) international development projects in 26 countries around the world, this book provides a scholarly analysis of their stories, identifies factors expatriate leaders experienced managing projects, then integrates the factors into a theory that explains and helps define the success, or lack thereof, they achieved, and provides recommendations on how to deal with and overcome the issues. For decades, international development projects have played a crucial role in the delivery of U.S. foreign aid and yet, while considerable attention has been given to policymakers' foreign aid decisions concerning which countries receive U.S. foreign aid and how much each country receives, scant attention has been given to understanding the challenges encountered by the expatriate leaders recruited to manage the implementation of these international development projects, which unfold within a confluence of diverse multi- organizational contexts and culturally complex developing country environments. Even less is known about what factors these expatriate leaders experience that could explain, and help define, the success, or lack thereof, they achieve managing the implementation of these projects. This book is essential reading for international development leaders, practitioners, and scholars, as well as foreign aid policymakers, as they seek to improve international development.
Includes index.
Keywords: United States. -- Agency for International Development -- Officials and employees.; Leadership.; Foreign executives.; Success in business.; International organization.; Business & Economics -- Management.; Project management.; elektronické knihy; electronic books